A kinematically based algorithm to estimate the energy cost of variable-speed shuttle running - Zago, M.; Galli, M.; Rampichini, S.; Limonta, E.; Esposito, F.; Sforza, C. (ISBS Proceedings Archive (Michigan), 2017)
Changes of direction (CoDs) have a high metabolic and mechanical impact in field and court team sports, but the estimation of the associated workload is still inaccurate. The aim of this study is to establish a kinematic-based algorithm to determine the energy cost of running at variable speed with frequent 180° CoDs. Kinematic and metabolic data were simultaneously collected during 5-minutes 5+5 m shuttle run tests. Mechanical work computation was split into positive (eccentric) and negative (concentric) contributions. When compared to the actual energy cost, the estimation algorithm returned an error of 5%. This model constitutes the theoretical basis to extend the model from the laboratory to the field, obtaining an accurate measure of the workload of training and matches.